Unravelling homeostasis effects of phosphorus and zinc nutrition by leaf photochemistry and metabolic adjustment in cotton plants - Santos, Elcio Ferreira; Pongrac, Paula; Reis, André Rodrigues [UNESP]; Rabêlo, Flávio Henrique Silveira; Azevedo, Ricardo Antunes; White, Philip J.; Lavres, José (Springer Nature, 2021)
Phosphorus (P) and zinc (Zn) uptake and its physiological use in plants are interconnected and are tightly controlled. However, there is still conflicting information about the interactions of these two nutrients, thus a better understanding of nutritional homeostasis is needed. The objective of this work was to evaluate responses of photosynthesis parameters, P-Zn nutritional homeostasis and antioxidant metabolism to variation in the P × Zn supply of cotton (Gossypium hirsutum L.). Plants were grown in pots and watered with nutrient solution containing combinations of P and Zn supply. An excess of either P or Zn limited plant growth, reduced photosynthesis-related parameters, and antioxidant scavenging enzymes. Phosphorus uptake favoured photochemical dissipation of energy decreasing oxidative stress, notably on Zn-well-nourished plants. On the other hand, excessive P uptake reduces Zn-shoot concentration and decreasing carbonic anhydrase activity. Adequate Zn supply facilitated adaptation responses to P deficiency, upregulating acid phosphatase activity, whereas Zn and P excess were alleviated by increasing P and Zn supply, respectively. Collectively, the results showed that inter ionic effects of P and Zn uptake affected light use and CO2 assimilation rate on photosynthesis, activation of antioxidant metabolism, acid phosphatase and carbonic anhydrase activities, and plant growth-related responses to different extents.